Sonographic Diagnosis of Periorbital Dermoid Cyst. Issue 1 (March 2017) - Whittle, Carolina; Retamal, Andres; Kramer, Daniela; Silva, Claudio
Abstract : Abstract: Periorbital dermoid cysts occur mainly in children. Sonography is useful for the noninvasive, nonionizing evaluation of soft tissue lesions in infants and children without requiring sedation or anesthesia. We report the sonographic appearance of 25 periorbital dermoid cysts and identified that all are avascular oval lesions located below the aponeurotic plane. Nonaggressive bone remodeling was present in 52% of the cases. These finding in pediatric periorbital lesions are highly suspicious of a periorbital dermoid cyst.